2016
DOI: 10.4103/0259-1162.177187
|View full text |Cite
|
Sign up to set email alerts
|

Evolving with modern technology: Impact of incorporating audiovisual aids in preanesthetic checkup clinics on patient education and anxiety

Abstract: Background and Aims:Perioperative stress is an often ignored commonly occurring phenomenon. Little or no prior knowledge of anesthesia techniques can increase this significantly. Patients awaiting surgery may experience high level of anxiety. Preoperative visit is an ideal time to educate patients about anesthesia and address these fears. The present study evaluates two different approaches, i.e., standard interview versus informative audiovisual presentation with standard interview on information gain (IG) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…Our results confirm that increasing patients’ information is necessary to improve their satisfaction [ 18 - 21 ] and knowledge [ 16 , 19 ], as well as to reduce their anxiety [ 22 - 25 ].…”
Section: Discussionsupporting
confidence: 77%
“…Our results confirm that increasing patients’ information is necessary to improve their satisfaction [ 18 - 21 ] and knowledge [ 16 , 19 ], as well as to reduce their anxiety [ 22 - 25 ].…”
Section: Discussionsupporting
confidence: 77%
“…Our results confirm that increasing patients' information is necessary to improve their satisfaction [18][19][20][21] and knowledge [16,19], as well as to reduce their anxiety [22][23][24][25].…”
Section: Renderxsupporting
confidence: 80%
“…Similar findings have been reported in the past. [ 19 ] However, it has also been observed that though information leaflets help patients get involved in the decision-making process, they may not influence outcome or satisfaction metrics. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, information gain has been shown to reduce patient anxiety. [ 19 ] Interestingly, Gillies and Baldwin reported that if provided in an inappropriate form, information leaflet can lead to anxiety. [ 21 ] Our study did not assess patient anxiety and is one of its limitation.…”
Section: Discussionmentioning
confidence: 99%